IN VITRO ANTIOXIDANT AND ANTI-ADIPOGENIC EFFECTS OF SLENDESTATM, STANDARD POTATO EXTRACTS CONTAINS 5% PROTEASE INHIBITOR II - Lee, Dae Geon; Park, Sang In; kang, Su Jin; Kim, Joo Wan; Lee, Eun Kyoung; Song, Chang Hyung; Han, Chang Hyun; Lee, Young Joon; Ku, Sae Kwang (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The objective of present study is to observe the anti-adipogenic effects of SlenestaTM (SLD), a standard potato protein extracts containing 5% potato protease inhibitor II (PI2) on the 3T3-L1 preadipocytes which are able to differentiate into mature adipocytes and accumulate lipids, as an obesity model with cytotoxicity and antioxidant effects. Materials and Methods: The cytotoxicity of SLD was observed against 3T3-L1 pre-adipocyte cell line by MTT assay, and also anti-adipogenic effects were observed through lipid accumulation assay during 3T3-L1 differentiation as comparing with N-Acetyl-L-cysteine (NAC). In addition, antioxidant effects of SLD were detected by free radical scavenging capacity and superoxide dismutase (SOD)-like activity as comparing with ascorbic acid. Results: SLD showed obvious cytotoxicity against 3T3-L1 pre-adipocyte cell line at higher concentrations, from 1.5 mg/ml for 72 hrs treatment, and cytotoxic IC50 of SLD after 24, 48 and 72 hrs treatment times were detected as 10.11 ± 0.67, 5.71 ± 0.37 and 5.34 ± 0.21 mg/ml, respectively. SLD concentration-dependently inhibited the lipid accumulations formatted during 3T3-L1 cell differentiations, and also effectively showed DPPH radical scavenging activity (IC50 = 161.98 ± 64.65 μg/ml) and SOD-like effects (IC50 = 284.54 ± 54.47 μg/ml). Conclusion: The results suggest that SLD effectively inhibited 3T3-L1 adipose cell differentiations may be through antioxidant activities and direct cytotoxicity in case of higher concentration, along with already known satiety effects mediated by increases of circulating cholecystokinin. These findings are considered as direct evidences that SLD may serve as a predictable functional ingredient for obesity as an alternative therapy.